Divalent metal modulation of Japanese flounder (Paralichthys olivaceus) purinergic P2X7 receptor - Carolina Paredes; Shuo Li; Xiaoli Chen; Claudio Coddou (FEBS Open Bio)
Paralichthys olivaceus P2X7 receptor (poP2X7R) is a recently identified as a P2X7 purinergic receptor involved in innate immunity of the Japanese flounder Paralichthys olivaceus. Divalent metals are allosteric modulators of mammalian P2XRs, but there is no information for fish P2XRs. Here, we characterized the effects of divalent metals on poP2X7R channel activity by electrophysiology and molecular biology techniques. Copper, zinc and mercury inhibited poP2X7R‐mediated currents with different maximal inhibition potency, while cadmium had no effect on poP2X7R activity. Mercury‐induced inhibition was irreversible, but the inhibitory effects of copper and zinc were reversed after washout. Cooper and zinc also reduced poP2X7R‐mediated interleukin‐1 mRNA production. These findings suggest that divalent metals have potential effects on the Japanese flounder innate immune response through modulation of poP2X7R activity.